Advances in biomarker development and potential application for preeclampsia based on pathogenesis. (January 2021) - Liu, Nan; Guo, Yu-Na; Gong, Li-Kun; Wang, Bing-Shun
Abstract: Preeclampsia (PE) is a pregnancy-specific complication that seriously threatens the health and safety of mothers and infants. The etiology of PE has not been fully elucidated, and no effective treatments are currently available. A pregnant woman with PE often has to make a tough choice on either endangering her own health to give a birth or being forced to terminate her pregnancy. It is recommended by the International Federation of Gynecology and Obstetrics that the combination of maternal high-risk factors and biomarkers could form a good strategy for predicting the risk of PE. Such a combination may also enable more effective monitoring and early clinical intervention in high-risk populations to reduce the risk of PE. Therefore, biomarkers validated by extensive clinical research may be formally applied for clinical PE risk prediction. In this review, we summarized data from clinical research on potential biomarkers and classified them according to the current four major hypotheses, namely placental or trophoblast ischemia and hypoxia, vascular endothelial injury, oxidative stress, and immune dysregulation. Additionally, we also discussed the underlying mechanisms by which these potential biomarkers may be involved in the pathogenesis of PE. Finally, we propose that multiple biomarkers reflecting different aspects of the disease pathogenesis should be used in combination to detect the high-risk PE population in support of clinically targeted intervention and prevention of PE. It is expected that tests made of more sensitive and reliable PE biomarkers based on the aforementioned major hypotheses could potentially improve the accuracy of PE prediction in the future.